Energy consumption of mobile agents in a wireless ad hoc network environment. Issue 2 (1st June 2013) - Holt, Alan; Huang, Chi‐Yu
Abstract : In this study the authors consider the energy consumption of mobile agents operating in wireless local area network (WLAN) environment. They present an energy model of an ad hoc WLAN based on the IEEE 802.11 standard and analyse both per‐device and WLAN‐wide energy consumption. With this model the authors investigate 'features' of the 802.11 protocol (such as frame fragmentation, preamble/header lengths and power‐save schemes) on energy consumption in the context of a mobile agent management domain. They also consider 'clustering' as a means of optimising energy consumption.